Lateral Fluid Percussion Injury Causes Sex-Specific Deficits in Anterograde but Not Retrograde Memory - Fitzgerald, Julie; Houle, Samuel; Cotter, Christopher; Zimomra, Zachary; Martens, Kris M.; Vonder Haar, Cole; Kokiko-Cochran, Olga N. (Frontiers in Behavioral Neuroscience, 2022)
Cognitive impairment is a common symptom after traumatic brain injury (TBI). Memory, in particular, is often disrupted during chronic post-injury recovery. To understand the sex-specific effects of brain injury on retrograde and anterograde memory, we examined paired associate learning (PAL), spatial learning and memory, and fear memory after lateral fluid percussion TBI. We hypothesized that male and female mice would display unique memory deficits after TBI. PAL task acquisition was initiated via touchscreen operant conditioning 22 weeks before sham injury or TBI. Post-injury PAL testing occurred 7 weeks post-injury. Barnes maze and fear conditioning were completed at 14- and 15-weeks post-injury, respectively. Contrary to our expectations, behavioral outcomes were not primarily influenced by TBI. Instead, sex-specific differences were observed in all tasks which exposed task-specific trends in male TBI mice. Male mice took longer to complete the PAL task, but this was not affected by TBI and did not compromise the ability to make a correct choice. Latency to reach the goal box decreased across testing days in Barnes maze, but male TBI mice lagged in improvement compared to all other groups. Use of two learning indices revealed that male TBI mice were deficient in transferring information from 1 day to the next. Finally, acquisition and contextual retention of fear memory were similar between all groups. Cued retention of the tone-shock pairing was influenced by both injury and sex. Male sham mice displayed the strongest cued retention of fear memory, evidenced by increased freezing behavior across the test trial. In contrast, male TBI mice displayed reduced freezing behavior with repetitive tone exposure. An inverse relationship in freezing behavior to tone exposure was detected between female sham and TBI mice, although the difference was not as striking. Together, these studies show that retrograde memory is intact after lateral TBI. However, male mice are more vulnerable to post-injury anterograde memory deficits. These behaviors were not associated with gross pathological change near the site injury or in subcortical brain regions associated with memory formation. Future studies that incorporate pre- and post-injury behavioral analysis will be integral in defining sex-specific memory impairment after TBI.